The future of management - Hamel, Gary. (Harvard Business School Press, 2007)
"In The Future of Management, world-renowned business sage Gary Hamel argues that organizations need bold management innovation now more than ever. The current management model - centered on control and efficiency - no longer suffices in a world where adaptability and creativity drive business success." "In his most provocative book to date, Hamel takes aim at the legacy beliefs preventing twenty-first-century companies from surmounting new challenges. With incisive analysis and vivid illustrations, he explains how to turn your company into a serial management innovator."--Jacket.